An Investigation of Mathematics and Science Questions in Entrance Examinations for Secondary Education Institutions in Turke - Incikabi, Lutfi (Journal of Baltic Science, 12(3),352-364, 2013)
This study aimed to investigate LDE mathematics and science questions in terms of cognitive requirements (knowing, applying and reasoning) and structural properties (conceptual, algorithmic and graphical). The methodology adopted in the current study was document analysis. The results of this study indicated that LDE science assessments emphasized conceptual questions, while mathematics questions were more algorithmic in structure. In addition, both mathematics and science items de-emphasized graphical representations. In terms of their cognitive requirements, both science and mathematics LDE items neglected the cognitive domain of reasoning. Moreover, science questions mostly met in the intersection of knowing and conceptual, while mathematics questions often required students to apply knowledge on algorithmic questions. This study also concluded that the distribution of question requirements differed from year to year. Some implications regarding the results included that implementing a nation-wide assessment that neglects graphical representations contradicts the target goal of the mathematics and science programs in Turkey. The fact that the LDE was designed to determine the level of students’ learning yet neglects reasoning questions also presents a contradiction to the curricular aims
Keywords: cognitive requirements, level determination examination, mathematics and science problems, structural properties